PENERAPAN ALGORITMA GREEDY DALAM MENCARI RUTE TERDEKAT LOKASI SPBU BERBASIS WEB - Indyah Hartami Santi; Devi Budianti (Melati Institute, 2023)
Determining the closest distance is often an obstacle to reach the destination in a short time by considering costs. Among them is the determination of the location of the nearest gas station from the campus. One of the methods used to determine the closest distance from campus to the nearest gas station location is by applying the Greedy algorithm. The nearest gas stations around the campus include Gedoq, Papungan, Kalimantan, Kebonrojo and Stadium gas stations. Based on the search results using the Greedy algorithm, information is obtained that, to reach the Gedog gas station, the trip from the campus passes through the religious court node with a distance of 1.1km. Meanwhile, to reach Kebonrojo gas station, the trip from campus passes through the SMK Telkom Brawijaya node with a distance of 1.3km.